Umbrellas can work under water: Using threatened species as indicator and management surrogates can improve coastal conservation. (5th December 2017) - Gilby, Ben L.; Olds, Andrew D.; Connolly, Rod M.; Yabsley, Nicholas A.; Maxwell, Paul S.; Tibbetts, Ian R.; Schoeman, David S.; Schlacher, Thomas A.
Abstract: Species surrogates, the use of particular species to index habitat condition or to represent ecological assemblages are commonly identified in many ecosystems, but are less tested, and therefore less employed in estuaries. Estuaries provide important ecosystem goods (e.g. harvestable species) and services (e.g. carbon processing, coastal armouring), but require protection from multiple human activities, meaning that finding surrogates for estuarine condition or faunal assemblages is a significant knowledge gap. In this study, we test the efficacy of the threatened estuary ray Hemitrygon fluviorum, as a suitable indicator of ecosystem condition and management umbrella surrogate species for conservation prioritisation and monitoring purposes within estuaries. We surveyed fish assemblages and ray presence at ten sites within each of 22 estuaries in southeast Queensland, Australia, using one hour deployments of baited video arrays. We then tested for correlations between ray presence, a series of environmental variables considered important to ecosystem management within estuaries (i.e. testing rays as indicator species), and the co-occurring fish species (i.e. testing rays as umbrella species). Estuary rays function as both umbrella species and ecological indicators of habitat status in subtropical Australian estuaries. As umbrellas, ray occurrence concords with elevated species richness. As ecological indicators, ray distribution concords with habitats of good water quality (especially low turbidity) and more natural vegetation remaining in the catchment. These results highlight the potential for other threatened aquatic vertebrates that are both readily detectable and that are reliable proxies for ecosystems status to be become useful management tools in estuaries. The protection of such large, threatened species in coastal seascapes allows managers to address multiple targets for conservation, especially; (1) protecting species of conservation concern; (2) maintaining diversity; and (3) protecting optimal habitats by better placing reserves. Graphical abstract: